The Taoist Pedagogy of Pathmarks Critical Reflections upon Heidegger, Lao Tzu, and Dewey - Yu, Jie (Spirituality, Religion, and Education, 2018)
Based on the intertwined complex conversations among Heidegger, Dewey, and Lao Tzu, this book explores the possibilities of the Taoist Pedagogy of Pathmarks as a clearing between truth and untruth, responding to the spiritual call of Tao as inaction and teaching as releasement. In this book, Yu provides a critical exploration of the rich dynamics in the "direct" conversations among the three great thinkers of east and west, highlighting the implications of their ideas for education throughout. As more educational researchers, teacher educators, and teachers recognize the limitations of didactic teaching-as-telling, the author brings an alternate pathway to light. .